Congenital left lobe megaly of liver resembling splenic pathology: a diagnostic dilemma confirmed bySPECT-CT of liver-spleen scan - Bhattacharjee, Puja; Mandal, Tapati; Quddus, Sharmin; Mutsuddi, Pupree; Akhter, Papia; Islam, Md Azharul; Md Ismail, -; Siddique, Abu Bakker; Islam, Reajul; Haque, Jasmine Ara (Bangladesh Journal of Nuclear Medicine, 2021)
Liver scintigraphy is a specialized nuclear medicine imaging technique used to diagnose hepatic pathological conditions as well as to assess the function of the liver. Itis also used to follow the progress of treatment of certain diseases. This procedure may be referred as liver-spleen scan because the spleen is alsoevaluateddue to its proximity and close functional relationship to liver.SPECT-CT correlation along with planar images increases the specificity of the test and can guide the physicians to rule outdiagnostic dilemma regarding certain hepatic & splenic diseases. Here, we present a case where the patient was initially suspected tohave splenomegaly with splenic hematomabut finally confirmedas unusuallyenlarged left lobe of liverand normal sized spleen with SPECT-CT of liver-spleen scan. Bangladesh J. Nuclear Med. 22(2): 161-165, Jul 2019